La cesárea segmentaria en el caso impuro - Monteverde, Victorio (1938)
This work after making a brief review of the evolution of the caesarean operations points out the relatively low number of operations realized in the maternity hospital of Parmenio Pinero, during 15 years, 104 in a total of 13.700 cases equal to 0,70 %. This signifies that all recourses are exhausted for the delivery to take place by natural route, ideal of the tocologist and he does not abandon this route although the case may require, pointing to a good statistics in this respect. It is demonstrated by the fact that the rest of the interventions do not result overloaded, which would necessarily gravitated the total mortalities, maternal and foetal, and it is not so : 0,40 % and 3 % respectively. Next the author determines the causes which have prompted the intervention and the conditions under which they were effected, classifying the cases in to pure, impure and infected. He considers the case is impure « when there exists prolonged work with opening of the membranes of the foetus or rupture of the amniotic sac for more than 6 hours repeated and suspected touches, or tentative vaginal manoeuvres, temperature less than 38° and alteration of the amniotic fluid». Coincidently, one gets the impression that the pure and impure cases show the same porcentage of maternal mortality, 2,12 %. The only case diagnosed as infected died. If the maternal mortality is low, the morbidity is high, 30 % for the pure cases, 51 % for the impure cases. The author attributes the good results to the technique of the caesarean section employed (that of Kraenig with slight variations) and the drainage of the impure cases. He confides that the morbidity will be better yet, with the modern technique of Michon, Leon, and «especially that of Marruz and Villalta, which he describes.